Hubungan Perubahan Tata Guna Lahan dengan Debit Air Limpasan pada Kawasan Hunian Pantai Indah Kapuk 2 - Alfianabila Yusfiaka; Etih Hartati; M. Candra Nugraha (Fakultas Teknik, 2020)
The construction of the residential and commercial area of Pantai Indah Kapuk (PIK) 2 Cluster “D” is located in the part of two sub-district, which is Sub-district of Kosambi and Sub-district of Teluknaga. PIK 2 Cluster “D” has an area of 508,59 Ha. With the construction of PIK 2 Cluster “D”, there will be a change of land use and an enchancement of run off water. The relationship between the change of land use and the enhancement of run off water can be seen from run off peak deviation for reset time T year (Qr) on existing condition with planning condition after the change of land use. The method used is the rational method which is estimating run off peak. There is an enhancement off run off coefficient value (C) on existing condition about 0,46 and 0,81 on planning condition which causing an enhancement off run off peak in planning area as the effect of the change of land use as Q = 87,59 m3/second. The enhancement of run off coefficient value as the effect of the change of land use is directly proportional with the enhancement of run off peak in case study residential and commercial area of PIK 2 Cluster “D”.